A new and informative [a, b, c, d] nomenclature for one-pot multistep transformations: a simple tool to measure synthetic efficiency. Issue 38 (11th June 2018) - Indu, Satrajit; Kaliappan, Krishna P.
Abstract : We propose a generalized and informative [a, b, c, d] nomenclature for various types of one-pot multistep reactions, which emphasizes the fundamental parameters that define the synthetic efficiency of such transformations. Abstract : Domino, cascade and tandem reactions constitute the most efficient and creative chemical transformations with a huge domain of synthetic utility and applications. A number of reactions may be achieved in a single pot, accompanied by the formation of new rings and new bonds, leading towards higher molecular complexity. A lack of one unified, yet informative descriptor often understates the synthetic ingenuity of certain highly creative transformations. In this review, we propose a new tetra-coordinated [a, b, c, d] nomenclature which takes into account and displays the basic parameters which generally indicate the level of efficiency of a chemical transformation. An almost exhaustive set of one-pot multistep reactions may be described by this system and this review is an attempt to display the one-pot multistep transformations reported from our group and to classify them based on our proposed descriptor.